Lean e green: a contribuição da produção enxuta e da gestão ambiental para a redução de desperdícios - Vasconcelos, Danilo Cavalcante de (2012)
In the highly competitive environment where companies are located, production systems can become a threat if the performance of their operational processes can not reduce costs, waste, control environmental impacts and increase productivity. In this scenario increases the search for new concepts and management practices as a strategy to suit the new demands of the competitive market. Within this context this research was developed with the main objective to investigate the relationship of complementarity between lean (Lean) and environmental management (Green) as a strategy for reducing waste in production processes. The approach was largely qualitative research carried out by means of multiple case study used in three companies of Ceará, from a sample drawn from a universe of 14 companies from different economic sectors, certified to ISO 14001 and using the lean production system associated with the practice of environmental management in its operational processes. The results produced evidence to indicate that the use of lean associated environmental management in the production process contributes to the reduction in waste.